GEOESTATISTICAL INTERPOLATION APPLIED IN THE SPATIALIZATION OF CHEMICAL ATTRIBUTES OF A RED-YELLOW LATOSOL - de Oliveira, A. R; Martins, R. N.; Lopes Júnior, J. G.; Santos, J. A. S.; Siqueira, W. C.; Abrahão, S. A. (Revista Brasileira de Engenharia de Biossistemas, 2018)
Precision agriculture (PA) has excelled in site-specific nutrient management targeted to soil fertility correction, plant nutrition and environmental impact reduction in the conventional agriculture. Thus, this study aimed at determining by ordinary kriging and co-kriging, the spatial variability of pH (H2O), P, K, Ca, and Mg in a Red-Yellow Latosol. The study was conducted in a 0.6 ha area in Januária, Minas Gerais state, Brazil. Soil samples were taken at the 0.00–0.20 m layer depth, using a regular grid with 72 points (6 x 6 m). In order to apply the co-kriging technique based on the correlation between the attributes, another sampling grid with 40 points was created. The data were evaluated by descriptive statistics; linear correlation and spatial variability analysis based on the adjustment of semivariograms. The best correlations were observed between the pH and Ca (0.65) and K and Mg (0.39) attributes. In general, with exception to Mg, the levels of all attributes evaluated are good according to the soil classification of Minas Gerais state and offer adequate conditions for agricultural crops development. Finally, the use of co-kriging allowed estimating with good reliability the values ​​of Ca and Mg when values ​​of pH and K were used as covariables.